The Cinderella syndrome: why do malaria-infected cells burst at midnight? - Mideo, N; Reece, SE; Smith, A; Metcalf, C (2013)
An interesting quirk of many malaria infections is that all parasites within a host - millions of them - progress through their cell cycle synchronously. This surprising coordination has long been recognized, yet there is little understanding of what controls it or why it has evolved. Interestingly, the conventional explanation for coordinated development in other parasite species does not seem to apply here. We argue that for malaria parasites, a critical question has yet to be answered: is the coordination due to parasites bursting at the same time or at a particular time? We explicitly delineate these fundamentally different scenarios, possible underlying mechanistic explanations and evolutionary drivers, and discuss the existing corroborating data and key evidence needed to solve this evolutionary mystery.